Pelatihan pemadaman api menggunakan alat pemadam api ringan pada masyarakat Desa Air Satan Musi Rawas Sumatera Selatan - Wijaya, Sapondra; Wibowo, Wahyu Dwi Ari; Roni, Roni; Susmini, Susmini; Soewito, Bambang (Penamas: Journal of Community Service, 2025)
Fire is one of the non-natural disasters that still has a high incidence rate in Indonesia. The primary issue is the low level of public awareness and discipline regarding the use of electrical appliances and stoves, which are often the primary triggers of fire incidents. Early intervention is crucial to prevent the spread of fire damage, one of which is through the use of Fire Extinguishers (APAR) by the first witnesses of the incident. However, initial studies indicate that the public’s knowledge and skills in using APAR are still very low. This community service activity aims to enhance the public’s capacity to use APAR through an educational approach and simulation-based training. The methods used include short educational sessions and direct fire extinguishing simulations using APAR and real flames. Evaluation is conducted through skill observation using checklists before and after the activity. The results of the activity show a significant improvement in participants’ ability to use APAR effectively. With this improvement, it is hoped that the community can perform initial fire-extinguishing actions independently before the fire grows larger or before emergency personnel arrive at the scene.